Dow Chemicals - Dow Chemical Company (Dow Chemical Company, 1920)
Volume providing an overview of products manufactured by the Dow Chemical Company plant in Midland, Michigan including industrial chemicals, pharmaceutical products, metal alloys, dyes, and insecticides. Each product is listed with a description of the physical and chemical characteristics of the substance, its uses, shipping classification, and packing information. The work is fully illustrated with black and white photographic prints and colorful reproductions of paintings by Arthur Henry Knighton-Hammond (1875-1970), a British artist who, in 1920, was commissioned by Herbert H. Dow (1866-1930) to create a series of paintings of the Dow Chemical Company headquarters in Midland.
Keywords: Dow Chemical Company; Chemical industry; Chemical plants; Corporations; Pharmaceutical industry; Alloys; Dyes and dyeing; Insecticides